(untitled) (Research, Society and Development, 2023)
Introduction: Researchers diverge in relation to the possible impact of the SARS-CoV-2 pandemic on the pattern of alcohol consumption among university students. The objective of this study was to compare the pattern of alcohol use among university students, one week before and three months after the beginning of the social isolation. Method: Quantitative and longitudinal study, with data collection carried out in two moments: in person on 9th, 10th and 11th of March, 2020; and online, between the months of June and July, 2020. The instruments used were sociodemographic questionnaire and the Alcohol Use Disorders Identification Test (AUDIT). Results: 165 students answered before the pandemic and 100, among this sample, answered during the pandemic, being these students the final sample of the study. Results showed reduction in the total AUDIT score between the two moments: before, the median score was 5.9 (standard deviation = 4.96) and during the pandemic, it was 2.7 (standard deviation = 3.64). There was a significant worsening in the “mental/emotional health”, which was associated with the decrease of AUDIT score (p < 0.001). Conclusion: The pattern of alcohol use showed reduction in the second moment compared to the first one. In addition, the worsening of mental health during the beginning of social isolation was associated with the change in the pattern of alcohol consumption. It is suggested that more research should be carried out as a way to monitor possible changes in mental health and in the pattern of alcohol use in this population.